2022
DOI: 10.1016/j.ijid.2022.01.025
|View full text |Cite
|
Sign up to set email alerts
|

The seroprevalence, waning rate, and protective duration of anti-diphtheria toxoid IgG antibody in Nha Trang, Vietnam

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…We previously measured the duration of protective immunity using 2-year cohort data in a well-vaccinated community in Vietnam. 45 This study showed that IgG remains above 0.1 IU/ml for 4.3 years (95%CI:3.5,5.3) after the fourth dose of DTP was given at 18 months of age. This result supports the recommendation for a school-entry booster dose.…”
Section: Discussionmentioning
confidence: 63%
“…We previously measured the duration of protective immunity using 2-year cohort data in a well-vaccinated community in Vietnam. 45 This study showed that IgG remains above 0.1 IU/ml for 4.3 years (95%CI:3.5,5.3) after the fourth dose of DTP was given at 18 months of age. This result supports the recommendation for a school-entry booster dose.…”
Section: Discussionmentioning
confidence: 63%
“…Nevertheless, 50% of the population >17 years of age were susceptible, which explains why all age groups have been recently affected by diphtheria ( 4 ). A school-entry booster dose will be recommended to prevent future cases because the infant immunization program appeared to create low immunity in school age children ( 15 ). Conversely, low immunity in preschool age children would be another reason for the recent epidemic in Quang Ngai Province.…”
Section: Discussionmentioning
confidence: 99%
“…We stratified age into 4 groups, 1–5, 6–17, 18–40, and 41–55 years of age; children attend primary through high school between the ages of 6 and 17 years in Vietnam. On the basis of previously obtained age-stratified seroprevalence in Vietnam ( 14 , 15 ), the required sample size for each age stratum was estimated to be 350, 400, 400, and 350, respectively, with 10% precision, a 3.5 design effect, and an 80% response rate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 510 subjects aged 0–55 years were recruited by simple random sampling based on population census data, and serum samples were collected from the participants. The detailed survey method is reported elsewhere [21]. Of the 510 participants, 100 were randomly selected and recruited in 2019 to compare the TNT and ELISA methods.…”
Section: Methodsmentioning
confidence: 99%